An Empirical Analysis on The Impact of Image, Value, Quality, and Satisfaction on Customer Loyalty - Aquarista, Willa (Journal of Multidisciplinary Issues, 2024)
Purposes - This study aims to examine the influence of four key variables—image, value, quality, and satisfaction—on customer loyalty. The research seeks to evaluate both the direct and indirect effects of these variables on customer behavior, focusing on how customer satisfaction mediates these relationships to foster long-term loyalty. Methodology - The research employs a quantitative approach using structured questionnaires distributed to a randomly selected sample of respondents. Data were collected to test ten hypotheses that explore the relationships between the variables. Statistical analysis, including hypothesis testing, was conducted to determine the significance of each relationship, supported by reliability and validity assessments. Findings - The findings reveal that while quality and image do not have direct impacts on loyalty, their effects are significant when mediated by perceived value and customer satisfaction. Specifically, the study confirms that customer satisfaction plays a crucial role in enhancing loyalty, with quality and value significantly contributing to customer satisfaction, which in turn influences loyalty. Novelty - This study contributes to the existing literature by providing empirical evidence of the complex interrelationships between image, value, quality, and satisfaction in shaping customer loyalty. It highlights the importance of indirect effects, demonstrating that satisfaction and value are key mediators in the process of building loyalty, particularly in industries where product differentiation is challenging. Research Implications - The research suggests that businesses aiming to improve customer loyalty should prioritize strategies that enhance perceived value and customer satisfaction. By consistently delivering high-quality products and services that meet customer expectations, companies can improve their brand image and foster stronger customer loyalty. Future studies should further explore the emotional and psychological dimensions of loyalty and their potential impact on consumer behavior.